The influence of NLC composition on curcumin loading under a physicochemical perspective and in vitro evaluation - Sousa Araujo, Victor Hugo; Silva, Patricia Bento da; Szlachetka, Isis Oliveira; Silva, Sebastiao William da; Fonseca-Santos, Bruno; Chorilli, Marlus [UNESP]; Ganassin, Rayane; Tavares de Oliveira, Giulia Rosa; Oliveira da Rocha, Marcia Cristina; Fernandes, Richard Perosa [UNESP]; Vieira Queiroz, Marjorie de Carvalho; Azevedo, Ricardo Bentes; et al. (Elsevier B.V., 2020)
The use of (nanostructured lipid carries) NLC to disperse curcumin in aqueous media is widely found in literature. However, few studies systematically analyze the influence of the lipid matrix composition and the presence of curcumin on the physicochemical characteristics of NLC. Thus, the present work aimed to verify the influence of the NLC composition on its structure. Different solid lipid (SL) to liquid lipid (LL) ratios were evaluated, yielding NLC < 600 nm and < 400 nm with the use of MCT and castor oil, respectively. The addition of Tween 80 favored the formation of smaller structures. Thermal analysis data confirmed the formation of different structures due to their different composition and also after the incorporation of curcumin. The present study also describes a correlation between the rheology of the NLC dispersion and the degree of structural organization of the NLC, indicating the formation of structures with a differentiated degree of organization. Photomicrographs showed the formation of two different structures, multiple types and amorphous, with drug concentrated in nucleus. in vitro studies have not shown significant IC50 differences between the systems developed with curcumin; however, the time and effectiveness of internalization were different for the two developed systems. The interaction between SL and LL demonstrated to be an important parameter that should be considered before the development of NLC, also the molecular characteristics of each component must be verified in order to develop NLC on a desirable type.
Keywords: Nanostructured lipid carrier; Curcumin; Composition influence